2022
DOI: 10.1038/s41531-022-00284-0
|View full text |Cite
|
Sign up to set email alerts
|

Change in the incidence of Parkinson’s disease in a large UK primary care database

Abstract: Parkinson’s disease (PD) has the fastest rising prevalence of all neurodegenerative diseases worldwide. However, it is unclear whether its incidence has increased after accounting for age and changes in diagnostic patterns in the same population. We conducted a cohort study in individuals aged ≥50 years within a large UK primary care database between January 2006 and December 2016. To account for possible changes in diagnostic patterns, we calculated the incidence of PD using four case definitions with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
0
17
1
Order By: Relevance
“…Second, dementia and PD tend to be underdiagnosed and under-recorded,32 44 which may lead to measurement errors in our outcomes and would tend to lead associations towards the null. We used both diagnosis and prescription records to define our outcomes which could lead to misclassification due to the off-label use of certain medications 45 46.…”
Section: Discussionmentioning
confidence: 98%
“…Second, dementia and PD tend to be underdiagnosed and under-recorded,32 44 which may lead to measurement errors in our outcomes and would tend to lead associations towards the null. We used both diagnosis and prescription records to define our outcomes which could lead to misclassification due to the off-label use of certain medications 45 46.…”
Section: Discussionmentioning
confidence: 98%
“…It has been ranked second neurodegenerative disorders worldwide just after Alzheimer's disease (AD) (1). Since its description over 200 years ago by James Parkinson, PD has shown the fastest rising prevalence of all neurodegenerative diseases worldwide (2,3). As reported in the Global Burden of Disease Study 2016, the prevalence and incidence of PD are observed in 1-2% of the population aged >60 years, which have not changed significantly in industrialized countries including the United States and UK, between 1990 and 2016 (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Since its description over 200 years ago by James Parkinson, PD has shown the fastest rising prevalence of all neurodegenerative diseases worldwide (2,3). As reported in the Global Burden of Disease Study 2016, the prevalence and incidence of PD are observed in 1-2% of the population aged >60 years, which have not changed significantly in industrialized countries including the United States and UK, between 1990 and 2016 (2,3). However, the global burden of PD has more than doubled to over 6 million as a result of increasing numbers of older people (4,5), with potential contributions from environmental factors and longer disease duration.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, dementia and PD tend to be under-diagnosed and under-recorded [32,44], which may lead to measurement errors in our outcomes and would tend to lead associations towards the null. We used both diagnosis and prescription records to define our outcomes which could lead to misclassification due to the off-label use of certain medications [45,46].…”
Section: Discussionmentioning
confidence: 98%